Fraud Analysis in the Corruption Case of PT. Waskita Karya Based on Ethical Principles and GCG Principles - Kurnia Asih, Dea; Supriyatna, Dede; Andita Fitriannisa, Eka; Meisya, Eveline; Nofriyanti (Universitas Pamulang, 2025)
This research aims to conduct a literature review of ethical principles and good corporate governance principles as well as business ethics regarding corruption cases at PT. Waskita Karya Tbk which has harmed many parties and also has an impact on public trust. Apart from that, this research also explains the factors that make this case possible. The research method used is a qualitative method and data collection is carried out through documentation from validated sources and literature studies. The results of this research conclude that in the literature, the fraud that occurred in this case was triggered by many things, such as fraud that was deliberately carried out and resulted in ethical issues and a lack of internal control. The solution offered is to strengthen the implementation of good corporate governance in company management and improve ethics from the lowest managerial level, up to the highest decision holders.